PENGARUH SELF IMAGE CONGRUITY DAN CUSTOMER PERCEIVED SERVICE QUALITY TERHADAP REPURCHASE INTENTION DI VEGAS BARBERSHOP DENPASAR - Ikadek Sumiarta; Anak Agung Putu Agung; Ni Putu Cempaka Dharmadewi Atmaja (VALUES, 2023)
Barbershop offers haircut services with a more modern concept, both current hairstyle trends and the tools used to cut hair. Barbershops provide services that are more private for men than salons which are mostly for women. Vegas Barbershop services not only provide haircuts but also provide services such as hair spa creambath, hair cosmetic, and hair toning, therefore Vegas Barbershop is very suitable for men's wants and needs for hair care. The research objective was to determine the effect of self congruity and customer perceived service quality on repurchase intention at Vegas barbershop Denpasar. The method in this study uses multiple linear regression analysis techniques. The results showed that Self Image Congruity had a positive and significant effect on Repurchase Intention at Vegas Barbershop in Denpasar City. Customer Perceived Service Quality has a significant positive effect on Repurchase Intention at Vegas Barbershop in Denpasar City. Respondents' responses to the self image congruty variable obtained the lowest score for the self image congruty variable which lies in the statement that I use the services of the Vegas Babershop in Denpasar City every time I cut my hair, it is hoped that the company's management will pay attention to and continue to improve the quality of services at Vegas Babershop to consumers so that consumers return to using Vegas Babershop services every time cut hair. Respondents' responses to the customer perceived service quality variable obtained the lowest score in the statement that I use the services of Vegas Barbershop Denpasar because the service is responsive to consumers. cut hair.